Penerapan Brain Gym Terhadap Tingkat Demensia Pada Lanjut Usia - Riyani Wulandari; Dewi Kartika Sari; Siti Fatmawati (Bima Nursing Journal, 2020)
The problem of dementia which is an intellectual impairment and memory in old age is a problem that needs to get immediate prevention and good handling. There are ways that can be used to prevent dementia, one of which is brain exercise, which is a series of simple movements that can balance the brain and is a training program to train the right and left brain nerve cells.This study aims to explain the effectiveness of brain exercise in reducing dementia levels in the elderly. The research design used a quasy experiment with a control group design pre-test-post-test. The population is the elderly who are active participants in Posyandu in the Pucangsawit Village area. The sample of this study was 50 respondents, taken using a random sampling technique with 25 respondents being the intervention group and 25 respondents being the control group, where these respondents had met the inclusion criteria set.The independent variable is brain gym and the dependent variable is the level of dementia in the parents. Data were collected using the SMMSE questionnaire. The results showed that there was an effect of the application of brain training on the level of dementia in the elderly, there was a significant decrease in the average level of dementia before and after the application of brain exercise in the intervention group, there was a significant decrease in the average level of dementia before and after the application of placebo in the control group. , there was a significant reduction in dementia rates (p value = 0.0001) in the intervention group after being given a brain gym. Further analysis showed a significant difference in the level of dementia among the elderly in the intervention group and the control group with a value of p = 0.013. Conclusion: brain exercise has a significant effect in reducing dementia rates in the elderly